Analisis Pengaruh Rasio Keuangan dan Ukuran Aset Pada Pertumbuhan Laba Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia Periode 2010-2013 - Dian Permata Sari; Hadi Paramu; Elok Sri Utami (UPT Penerbitan Universitas Jember, 2017)
This article aims to analyze the influence of financial ratios and asset size on the earning growth of manufacture companies.60 manufature companies listed in the Indonesia Stock Exchange in 2010-2013 were selected as samples.using simple randomsampling method. Data analysis method used was multiple linear regression analysis. The results showed that only partiallyReturn on Assets influences the earning growth, while the current ratio, total asset turnover, debt ratio, earnings per share anda dummy variable (asset classes) do not influence on earning growth. This informs that the company's earning growth could beindicated by Return on Assets while other financial ratios and asset size could not provide a signal for company's earninggrwoth.